A feedback inhibition between miRNA-127 and TGFβ/c-Jun cascade in HCC cell migration via MMP13. - Zhihong Yang; Yuxia Zhang; Li Wang (PLoS ONE)
Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide and is increasing in frequency in the U.S. The major reason for the low postoperative survival rate of HCC is widespread intrahepatic metastasis or invasion, and activation of TGFβ signaling is associated with the invasive phenotype. This study aims at determining the novel function of miR-127 in modulating HCC migration. Overexpression of miR-127 inhibits HCC cell migration, invasion and tumor growth in nude mice. MiR-127 directly represses matrix metalloproteinase 13 (MMP13) 3'UTR activity and protein expression, and diminishes MMP13/TGFβ-induced HCC migration. In turn, TGFβ decreases miR-127 expression by enhancing c-Jun-mediated inhibition of miR-127 promoter activity. In contrast, p53 transactivates miR-127 promoter and induces miR-127 expression, which is antagonized by c-Jun. The inhibition of miR-127 by c-Jun is through TGFβ-mediated ERK and JNK pathways. The lower miR-127 expression shows a negative correlation with the higher MMP13 expression in a subset of human HCC specimens. This is the first report elucidating a feedback regulation between miR-127 and the TGFβ/c-Jun cascade in HCC migration via MMP13 that involves a crosstalk between the oncogene c-Jun and tumor suppressor p53.